Presidents, diplomats, and other mortals essays honoring Robert H. Ferrell - Clifford, J. Garry (John Garry), 1942-; Wilson, Theodore A., 1940-; Ferrell, Robert H. (University of Missouri Press, 2007)
"Examining the role of the United States in the international arena from the 1860s to the present, these essays in honor of Robert H. Ferrell consider presidents from Lincoln to Bush, as well as the success or failure of diplomatic efforts in Russia, Nicaragua, Saudi Arabia, Iran, Iraq, and elsewhere"--Provided by publisher.